The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1302/0301-620x.103b6.bjj-2020-2401.r1
|View full text |Cite
|
Sign up to set email alerts
|

2021 Chitranjan S. Ranawat Award: Intraosseous vancomycin reduces periprosthetic joint infection in primary total knee arthroplasty at 90-day follow-up

Abstract: Aims Infection complicating primary total knee arthroplasty (TKA) is a common reason for revision surgery, hospital readmission, patient morbidity, and mortality. Increasing incidence of methicillin-resistant Staphylococcus aureus (MRSA) is a particular concern. The use of vancomycin as prophylactic agent alone or in combination with cephalosporin has not demonstrated lower periprosthetic joint infection (PJI) rates, partly due to timing and dosing of intravenous (IV) vancomycin administration, which have prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…In this study, despite the fact that a daily dose of LMWH for 3 days and then transitioning to low-dose aspirin for 2 to 5 weeks was considered a less aggressive strategy 10 , 11 , 21 , 22 , we still observed the association between pharmacological prophylaxis and early postoperative infection events. The postoperative 30 and 90 days were two common time points to evaluate the early postoperative complications, including SSC and PJI 23 – 25 . Notably, pharmacological thromboprophylaxis was associated with multiple outcome domains in the early postoperative period, including 90-day readmission for SSC, PJI, and all 90-day PJI events.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, despite the fact that a daily dose of LMWH for 3 days and then transitioning to low-dose aspirin for 2 to 5 weeks was considered a less aggressive strategy 10 , 11 , 21 , 22 , we still observed the association between pharmacological prophylaxis and early postoperative infection events. The postoperative 30 and 90 days were two common time points to evaluate the early postoperative complications, including SSC and PJI 23 – 25 . Notably, pharmacological thromboprophylaxis was associated with multiple outcome domains in the early postoperative period, including 90-day readmission for SSC, PJI, and all 90-day PJI events.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study of 1,060 patients undergoing primary TKA, Park et al observed a sixfold decrease in PJI at a minimum 90-day follow-up with intraosseous vancomycin compared with intravenous vancomycin as an adjunct to intravenous cefazolin administered to all patients 67 . In a multicenter, retrospective cohort study of 1,906 patients who underwent a primary TKA, Parkinson et al found a lower risk of PJI within 1 year postoperatively with prophylactic antibiotics administered intraosseously and intravenously compared with those administered only intravenously 68 .…”
Section: Antibioticsmentioning
confidence: 99%
“…Injection of a lower dose (500 mg of vancomycin) mixed with 120 mL of normal saline achieves 6-10 times the tissue levels of a standard dose given systemically [29,30]. There is emerging evidence of a reduction in PJI with intraosseous vancomycin use without increased risk of complications [31,32].…”
Section: How Should Antibiotics Be Administered?mentioning
confidence: 99%